Schistosomiasis mansoni in families of fishing workers of endemic area of Alagoas - Andrea Gomes Santana de Melo; José Jenivaldo de Melo Irmão; Verónica de Lourdes Sierpe Jeraldo; Cláudia Moura Melo (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To analyze the epidemiological and clinical aspects involved in the transmission and manifestation of schistosomiasis in a community of fishermen from the endemic area of Alagoas. Methods: Epidemiological, transversal, prospective, descriptive, quantitative study. The coproparasitological survey included 275 family units of fish workers and the epidemiological and clinical ones, those with a positive diagnosis for S. mansoni. Results: The prevalence of schistosomiasis was 13.9% (fishermen), 2.1% (shellfish) and 2.1% (family members). The occurrence of the infection varied according to gender, age, ethnicity and socioeconomic status. Exposure occurred near the home. Autochthonous and predominant low parasite burden, intestinal clinical presentation, abdominal pain and diarrhea were observed. There were no nutritional and pressure changes associated with parasitosis. Adherence to drug therapy and use of the schistosomicidal drug was feared. Conclusion: Fish workers are at high risk for contracting the disease with clinical hepatointestinal manifestation, which requires more intense health actions.